A fundamentação da ciência da natureza humana de David Hume: uma epistemologia experimental - CAMPELO, Wendel de Holanda Pereira (Universidade Federal do Pará, 2014)
The science of human nature is the Hume’s project concerning to all his philosophy – aesthesis, ethic, politic, theory of knowledge, history, economy, philosophy of religion etc. -; matter that we never could to account, because of the nature of a work of master’s degree. Hence, we just content ourselves to talk about to the foundation of science of human nature, concerning to the research about the origin of ideas and operations of understanding, or about the research regarding the causes and occult powers of human understanding, based on experimental method. The question that ours work seek to explain is closely this: What is a science of human nature based on experimental method? This one will, therefore, ours task from now on. We regard, from a holistic and scientific approach of human mind, Hume tries to explain the nature of powers or intellectual faculties, mainly its boundaries and weakness. Being, hence, the base of the science of man the experimental method that, in turn, has its solid foundation on the experience and observation; we must, then, to ask: how and to what extend the use of a such method became indispensable to the moral philosophy – that is, to the philosophical questions altogether – and that it touch on science of human nature? To know it is to know the initial step of philosophical Humean project, that is, the study of human understanding that, on the other hand, it is subdivided in two moments, viz, (1) the science of man, by which Hume shows the boundaries of ours faculties and intellectual powers and (2) the skepticism that is, then, the outcome this study, the finding of weakness and boundaries of human understand. In this sense, we feel free to talk about some account both of Treatise as first Enquiry, many times indistinctly, trying to emphasize that such works, when compared, can to reveal the maturation of a same philosophical project that is the science of human nature. And this is exactly this tread of ours research: how a science of human nature is projected by Hume and to what extend is possible to talk to maturation of its purposes? With this initial exam, we will be able to answer some problems concerning to the view by which Hume was appointed like radical skeptical. We will show why the critique regarding his “theory of ideas” taken by philosophers of common sense does not regard important points of his science of mind, generating many misunderstanding for posterity.In short, in the Chapter 1 of this work, we will examine what it was the Hume’s philosophical project and, by means of this exam, we will try to show, in the Chapter 2, the bases in which this science of mind constructed by Hume is sustained. In the Chapter 3, we will show that the interpretation skeptical-destructive of the posterity is misguided, in that it disregard the means found by Hume to his foundation of the science of human nature.